Removal of Ni(II) and Cu(II) in Aqueous Solutions Using Treated Water Hyacinth (Eichhornia crassipes) as Bioadsorbent - Carlos González-Tavares; Mercedes Salazar-Hernández; Alfonso Talavera-López; Juan Manuel Salgado-Román; Rosa Hernández-Soto; José A. Hernández (Separations, 2023)
Phytoremediation consists of taking advantage of the capacity of certain plants to absorb, accumulate, or metabolize contaminants. In this study, Eichornia crassipes (water lily) treated with water (WLW) and NaOH (WLN) was investigated as an adsorbent for removal of Ni(II) and Cu(II) present in aqueous solution, focusing on determining the most efficient conditions (adsorbent concentration, contact time, pretreatment, temperature). The results showed that equilibrium adsorption was favorable and carried out by a multilayer physical process with both bioadsorbents. The maximum adsorption at 30 °C in WLW and WLN was 349 and 293.8 mg/g of Ni(II), respectively, and 294.1 and 276.3 mg/g of Cu(II), respectively. The thermodynamic analysis indicated that the removal in both metals was spontaneous and exothermic. The Avrami model was the most adequate in the kinetic study of Ni(II) and Cu(II) removal in both treatments, which revealed that the adsorption process was carried out by several mechanisms. In the characterization of the adsorbents, it was determined that the functional groups of WL as well as the attractive forces on the surface of the materials participated in the metal removal process.